Lymphedema due to Podoconiosis in Brazil - Godoy, José Maria Pereira de; Godoy, Henrique José Pereira de; Godoy, Lívia Maria Pereira de (Brazilian Journal of Case Reports, 2024)
Podoconiosis is a neglected tropical disease that causes a type of progressive, non-infectious tropical lymphedema. Aim: The aim is reported one case of the one woman that presented always having problems with allergies and “lumps” appeared on the hallux of the right foot; it resembled a callus, which never disappeared and increased in size. The physical exam revealed several hardened nodular lesions in both feet involving the soles. The patient was submitted to intensive treatment for lymphedema using the Godoy Method® for the lower limbs for five days. The nodules were hardened and constant from the beginning. However, intensive treatment led to a reduction in the volume of the lesions, enabling better plantar flexion and extension as well as a gain in ambulation. However, the characteristics of the evolution of the condition, symptoms and the occurrence of nodules on velvety skin with a mossy kept appearance because are characteristics of podoconiosis. Podoconiosis may have other causes beyond those reported in literature, likely related to the exposure of the limb and associated immunological abnormalities.